La risa, regulador social de los estados emocionales y la ﬁjación del aprendizaje - Rojas de la Puente, Edward Enrique (2018)
The following “Theoretic proposal called: the laughter as the real emotional regulator,social and ﬁxing of learnings” this study is conclusive in three fundamental principles: thelaughter is an emotional regulator, the laughter is a social regulator, the laughter is a ﬁxinglearning. This was proved with students from the Toribio Rodríguez de Mendoza NationalUniversity of Amazonas – Peru and groups of people in study.The study was ethnographic-qualitative, with IAP or Participative Action Research. Themethodology was based on the transactional method. We used the qualitative method. Withits own qualitative categorizations of the social science. The technique were the observationand analysis. The data about the eﬀect to arrive to those principles were collected withinstruments as the structured interview, a notebook and ﬁlms. I can deduce that this is acontribution to the diﬀerent kinds of socio-educative disciplines and others because we getnew principles mentioned in the ﬁrst lines; which represents a theoretic contribution inteaching and learning.This study is made with a test and posttest design and with fortuitous groups whoseobjective is appreciate the real eﬀect of laugh. This research with a value to education,sociology and others sciences that study the human being. In conclusion: the laugh moderatethe emotions, the laugh moderate the social relationship and ﬁnally the laugh is a ﬁxer ofcomplex learning. The following research project was made in the Awajun ethnic inAmazonas region (out in the north-eastern part of Peru).Keywords: didactic technique, laughter, ﬁxation and retention.